Inhibition of cell growth by cellular differentiation into adipocyte-like cells in dexamethasone sensitive cancer cell lines. Issue 3 (4th May 2018) - Kim, Hea-In; Moon, Sun-Ha; Lee, Won-Cheol; Lee, Hyeon-Jeong; Shivakumar, Sharath Belame; Lee, Sung-Ho; Park, Bong-Wook; Rho, Gyu-Jin; Jeon, Byeong-Gyun
ABSTRACT: The stress responses in human body lead to secretion of cortisol hormone. The present study investigated the cellular responses on cell growth and cellular differentiation into adipocytes by exposure of synthetic stress hormone, dexamethasone (DEX) in various human cancer and normal cells. After prolonged exposure of cells with 1 μg/ml DEX for 2 weeks, population doubling time (PDT) was significantly ( P  < .05) increased by inhibited cell growth in A-549 and MCF-7 cancer cells, and was unchanged in MDA-MB-231 cancer cells, normal MRC-5 fibroblasts, umbilical cord matrix-derived mesenchymal stem cells (UCMSCs) and dental papilla tissue-derived mesenchymal stem cells (DSCs). Whereas, PDT was significantly ( P  < .05) decreased in U87-MG cancer cells by increased cell growth. Glucose uptake was significantly ( P  < .05) increased in all the cancer cell lines compared to that in normal cell lines. Further, adiposome-like vesicles were noted in A-549 and MCF-7 cancer cells indicating retarded cell growth by DEX treatment, and the vesicles were stained with Oil-Red O solution. Further, the expression of adipocyte-specific genes such as glucose transporter type 4 (GLUT4), glucocorticoid receptors β (GR β ) and peroxisome proliferator-activated receptor γ (PPAR γ ) were significantly ( P  < .05) increased in A-549 and MCF-7 with lipid vesicles. The level of telomerase activity was found to be significantly ( P  < .05) downregulated in DEX-treated A-549 and MCF-7 cancer cells. Our results have clearly shown that DEX treatment induces inhibition of cell growth by differentiating into adipocyte-like cells in dexamethasone sensitive cancer cells.